Ibn Kathir's Critical View of the Events of Islamic Conflicts and Seditions in "Al-Bidayah wa al-Nihayah": An Analytical Study - Mohammed Hussein Khalaf (Pubmedia Social Sciences and Humanities, 2025)
Islamic history, since the dawn of Islam, has formed a fertile ground for research and criticism due to the decisive events that have profoundly impacted the collective consciousness of the Muslim ummah. In this context, our study aims to explore the critical methodology followed by Ibn Kathir in "Al-Bidaya wa'l-Nihaya" and examine his stance on the companions and Islamic sects during the civil wars. The research problem revolves around the nature of Ibn Kathir's critical perspective, the criteria he used in criticizing the narratives, and the extent to which his doctrinal views influenced his presentation and analysis of events. Our findings show that Ibn Kathir provided a balanced and objective critical analysis of the fitan (seditions), combining various reports and weighing them scientifically, ensuring fairness in dealing with the events. Ibn Kathir aimed to help the ummah derive lessons from these fitan rather than using them as a means of political or sectarian incitement. Based on these findings, we recommend conducting independent studies on the impact of historical fitan on the unity of the Muslim ummah and how to prevent the recurrence of such divisions in the present day. Researchers and intellectuals should also contribute to the objective and scientific critique of historical heritage, in the same manner as Ibn Kathir did in his treatment of the major fitan